What's the economy trying to tell you? everyone's guide to understanding and profiting from the economy - Blitzer, David M. (McGraw-Hill, 1997)
Information about the economy is everywhere, but few people really understand it. Here's a savvy, jargon-free book that really makes sense of those confusing economic indicators. Written by the chief economist of Standard & Poor's, it shows readers exactly what to look for in order to make smart decisions about choosing stocks, buying real estate, evaluating career options, and more. Thoroughly updated to reflect current events and now available in paperback, this new edition is sure to be an indispensable resource for investors everywhere.